An Intergenerational Model of Inclusive Leadership in the Contemporary Church - Ana Budi Kristiani; Vian Klasia Wenno (Jurnal Teologi (JUTEOLOG), 2026)
The phenomenon of generational gaps within the church has emerged as a critical issue affecting leadership sustainability, particularly in Presbyterian traditions that tend to function in a monogenerational pattern. Empirical studies indicate that the dominance of senior generations within church governance structures has contributed to the marginalization of younger members, resulting in decreased participation in ministry and, in some cases, church disengagement. Survey data from Bilangan Research Center (2018) and a report from the Indonesian Ministry of Religious Affairs (2019) reveal that more than half of Christian youth in Indonesia perceive church programs and leadership patterns as increasingly irrelevant to their context.This article aims to examine the causes, impacts, and potential solutions to generational disparities in the church by proposing an intergenerational model of inclusive leadership. Employing a qualitative descriptive approach based on literature review, the study finds that generational gaps are shaped by differences in values, communication styles, leadership expectations, and perspectives on social issues. These differences have led to youth alienation, internal tensions in worship practices, stagnation in leadership succession, and declining congregational engagement.To address these challenges, this study proposes a constructive framework of inclusive leadership that includes: (1) the implementation of multigenerational leadership structures, (2) the cultivation of reciprocal mentoring culture, (3) the creation of intentional intergenerational dialogue spaces, and (4) the development of inclusive worship practices through blended styles and multigenerational ministry teams.The findings underscore that inclusive leadership is not merely an optional strategy but an urgent ecclesiological necessity for the contemporary church. By embracing an intentional intergenerational model, churches can bridge generational divides, enhance cross-generational participation, and sustain ministerial relevance amid rapid societal change, while remaining grounded in their theological identity.